Western environment/lifestyle has increased global genome methylation and decreased global gene expression in Chinese immigrants living in Australia - Zhang, Guicheng; Wang, K.; Schultz, E.; Khoo, S.; Zhang, X.; Annamalay, A.; Laing, I.; Hales, B.; Goldblatt, J.; le Souëf, P. (Wiley-Blackwell Publishing Asia, 2015)
Introduction: Several human diseases and conditions are disproportionally distributed in the world with a significant “Western-developed” vs. “Eastern-developing” gradient. Methods: We compared genome-wide DNA methylation of peripheral blood mononuclear cells in 25 newly arrived Chinese immigrants living in a Western environment for less than 6 months (“Newly arrived”) with 23 Chinese immigrants living in the Western environment for more than two years (“Long-term”) with a mean of 8.7 years, using the Infinium HumanMethylation450 BeadChip. In a sub-group of both subject groups (n = 12 each) we also investigated genome-wide gene expression using a Human HT-12 v4 expression beadChip. Results: There were 62.5% probes among the total number of 382,250 valid CpG sites with greater mean Beta (β) in “Long-term” than in “Newly arrived”. In the regions of CpG islands and gene promoters, compared with the CpG sites in all other regions, lower percentages of CpG sites with mean methylation levels in “Long-term” greater than “Newly arrived” were observed, but still >50%. The increase of methylation was associated with a general decrease of gene expression in Chinese immigrants living in the Western environment for a longer period of time. After adjusting for age, gender and other confounding factors the findings remained. Conclusion: Chinese immigrants living in Australia for a longer period of time have increased overall genome methylation and decreased overall gene expression compared with newly arrived immigrants.